The mechanisms of technological innovation in SMEs: a Bayesian Network Analysis of EU regional policy impact on Polish firms - Florio, Massimo; Parteka, Aleksandra; Sirtori, Emanuela (Technological and Economic Development of Economy, 2018)
We study the underlying mechanisms of technological innovation in SMEs in the context of ex-post evaluation of European Union’s regional policy. Our aim is to explain the observed change in firms’ innovativeness after receiving EU support for technological investment. To do so, we take an approach that is novel in innovation studies: a Bayesian Network Analysis to assess the effectiveness of EU policy instrument for technological innovation and to determine the mechanisms by which the policy works within firms. Our data draw from a unique survey of 200 Polish firms that received “Technological Credit” during the 2007−2013 programming period. First, we confirm the short-term positive impact of the EU innovation policy (i.e. a wider range of products/services offered, increased sales and exports). More importantly, we determine the causal chain between economically quantifiable outcomes and behavioural change in the firm, which is an important node in the network of effects generated. We find that only the financially sounder and more internationalised firms managed to take advantage of the policy. These findings suggest that programmes based on technological credits are not well suited to foster innovation in more fragile and domestically oriented SMEs, which may require different policy instruments.